Indexing Android Mobile Malware - Intan Nurfarahin Ahmad; Farida Hazwani Mohd Ridzuan; Madihah Mohd Saudi; Sakinah Ali Pitchay (Medwell Journals, 2024)
The increasing number of smartphones users have resulted in highly distributed applications that allow users to access information and resources from all over the world. With the advancement of technology, the attacker had created more sophisticated techniques that gave negative impacts to the smartphone users. Moreover, current techniques in mobile malware classification and detection having difficulties to detect the new advanced malware exploitation and threats. Therefore, an efficient mobile malware classification and detection technique are needed. In this research study, a new mobile malware classification and detection technique have been developed and evaluated. Based on the evaluation conducted, the result showed that the current mobile malware available in market is using different technique to avoid from being detected. Therefore in this research study, a way forward to detect such mobile malware is further discussed. Furthermore, the developed mobile malware classification and detection is used as the input for the indexing android mobile malware a framework for indexing android mobile malware also is documented in this research study.